Pendidikan Pesantren dalam Bingkai Pendidikan Nasional - Asmuni, Hadiqoh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2019)
Islamic boarding schools are the oldest Islamic educational institutions in Indonesia and make important contributions in the socio-religious field. Islamic boarding schools as educational institutions are able to maintain and maintain their survival (survival system) and have multi-aspect education. Islamic boarding school education needs to be developed and adapted to what is set by